The Influence of Learning Organization and Transformational Leadership on Teacher’s Innovative Work Behaviour through Self-Efficacy - Febrina Hariana Gultom; Ronald Suryaputra; Dany Moenindyah Handarini (FKIP - Universitas Riau, 2026)
Improving instructional quality at the secondary education level requires teachers to demonstrate sustained innovative work behavior. However, various organizational development initiatives and leadership practices in schools do not always translate into consistent instructional innovation among teachers. This study aims to examine the influence of Learning Organization and Transformational Leadership on teachers’ Innovative Work Behavior through Self-Efficacy in the context of SMP Kristen Kalam Kudus Malang. A quantitative approach was employed using a census technique involving 34 teachers, with data collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that Learning Organization has a significant effect on teachers’ Self-Efficacy, while Transformational Leadership does not significantly influence either Self-Efficacy or Innovative Work Behavior. Self-Efficacy has a significant effect on Innovative Work Behavior and mediates the relationship between Learning Organization and teacher innovation. Analysis of Self-Efficacy indicators shows that mastery experience, reflected through self-directed reflection on teaching practice, is the most dominant source of Self-Efficacy, whereas vicarious experience and social persuasion function as relatively weaker supporting factors. These findings highlight that teacher innovation is primarily driven by professional confidence developed through successful and consciously reflected teaching experiences within a learning-oriented organizational environment.